Erscheinungsformen und Handhabungen Heiliger Schriften - Quack, Joachim Friedrich (Materiale Textkulturen, 2014)
This study focuses on Holy Scriptures as material objects. What are the contexts for the appearances and the usages of these objects? Is there a difference between Holy Scriptures and other objects, and is it inevitably their sacred content that renders them holy? Interdisciplinary perspectives offer new incentives for understanding the material phenomenon of the 'Holy Scriptures'.